Direct and indirect effects of smoking during pregnancy on child development: The Japan Environment and Children’s Study - Nozomi Tatsuta; Kunihiko Nakai; Makiko Sekiyama; Yu Taniguchi; Miyuki Iwai-Shimada; Mai Takagi; Yayoi Kobayashi; Tomohiko Isobe; Shoji F. Nakayama; Shin Yamazaki; The Japan Environment and Children’s Study Group (Scientific Reports)
Abstract Maternal smoking during pregnancy is known to have an adverse impact on child development. This study aimed to elucidate whether maternal smoking during pregnancy has a direct adverse effect on the child development or whether it exerts an indirect effect through birth weight reduction or cadmium exposure. Mothers and infants enrolled in the Japan Environment and Children’s Study were evaluated. A total of 4794 mother–child pairs were included in the analysis. They were classified into four groups according to their smoking status during pregnancy (non-smokers [Q1, n = 2966], ex-smokers who quit before pregnancy [Q2, n = 575], ex-smokers who quit during pregnancy [Q3, n = 505] and smokers [Q4, n = 168)]). Children’s development was assessed at 2 and 4 years of age using a standardized tool, the Kyoto Scale of Psychological Development. Among male children, Q1 exhibited higher scores in all domains except posture-motor than Q4. Female children did not show lower scores in Q4 relative to the other groups. Path analysis revealed that maternal smoking increased cadmium exposure, a direct negative effect of maternal smoking was observed. The findings of this study confirm that maternal smoking during pregnancy has a direct negative impact on the development of children, particularly males.